A honeymoon in Brazil: the spawning behavior of an exotic reef fish in the western south Atlantic - Osmar J Luiz; Ivan Sazima; Luis F Waib; Carlos Eduardo L Ferreira (Neotropical Ichthyology)
The reproductive strategies of surgeonfishes of the genus Acanthurus are well known for all Atlantic species except the Monrovia doctorfish, Acanthurus monroviae, an eastern Atlantic surgeonfish whose biology remains largely unknown. We provide here the first account on the spawning behavior of A. monroviae, an exotic fish on rocky reefs of southeastern Brazilian coast.